The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1371/journal.pntd.0011022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of helminths and anthelmintic treatment on cardiometabolic diseases and risk factors: A systematic review

Abstract: Background Globally, helminth infections and cardiometabolic diseases often overlap in populations and individuals. Neither the causal relationship between helminth infections and cardiometabolic diseases nor the effect of helminth eradication on cardiometabolic risk have been reviewed systematically in a large number of human and animal studies. Methods We conducted a systematic review assessing the reported effects of helminth infections and anthelmintic treatment on the development and/or severity of card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 111 publications
(545 reference statements)
0
2
0
Order By: Relevance
“…volvulus ), blood pressure and cardiovascular hemodynamics, but none concerned loiasis [ 28 ]. Of the 18 studies included in this systematic review, 56% reported no effect; furthermore, anthelmintic treatment across three studies did not demonstrate any subsequent change in blood pressure [ 29 ]. In this study population, less than 2% of the population exhibited malaria parasites in their blood and no association with arterial was observed.…”
Section: Discussionmentioning
confidence: 99%
“…volvulus ), blood pressure and cardiovascular hemodynamics, but none concerned loiasis [ 28 ]. Of the 18 studies included in this systematic review, 56% reported no effect; furthermore, anthelmintic treatment across three studies did not demonstrate any subsequent change in blood pressure [ 29 ]. In this study population, less than 2% of the population exhibited malaria parasites in their blood and no association with arterial was observed.…”
Section: Discussionmentioning
confidence: 99%
“…The current review showed that the report of helminthic infections was lower than protozoa infections, and that these results were in line with the hypothesis concerning the association of IPIs (especially helminths) with diabetes explaining the beneficial role of helminths against metabolic syndrome. 61 , 62 …”
Section: Discussionmentioning
confidence: 99%